Achieving Record High External Quantum Efficiency >86.7% in Solar‐Blind Photoelectrochemical Photodetection (Adv. Funct. Mater. 28/2022). (11th July 2022) - Liu, Xin; Wang, Danhao; Shao, Pengfei; Sun, Haiding; Fang, Shi; Kang, Yang; Liang, Kun; Jia, Hongfeng; Luo, Yuanmin; Xue, Junjun; Wang, Jin; Zhi, Ting; et al.
Abstract : Solar‐Blind Photoelectrochemical Photodetectors In article number 2201604, Haiding Sun, Junjun Xue, Jin Wang, and co‐workers present a high‐efficient solar‐blind photoelectrochemical photodetector based on wide‐bandgap AlGaN nanowires, which are strategically decorated with Rh–Cr2 O3 hybrid structures. By virtue of the synergetic effect that optimizes the interfacial carrier behaviors after surface renovation, the device exhibits a record high external quantum efficiency of 86.7% with a responsivity over 178 mA W −1 .